‘More evolved than you’: Evolutionary spirituality as a cultural frame for psychedelic experiences - Evans, Jules (Frontiers in Psychology, 2023)
One of the dominant cultural frames for psychedelics in western culture over last 130 years has been evolutionary spirituality. This tradition suggests human evolution is not finished and can be guided towards the creation of higher beings through such techniques as psychedelics and eugenics or genetic modification. But is everyone evolving, or just the elite? This essay defines the tradition of evolutionary spirituality and points to five of the ethical limitations of the tradition – its tendency to spiritual narcissism, contempt for the less-evolved masses, Social Darwinism and Malthusianism, spiritual eugenics, and illiberal utopian politics – before suggesting responses to these limitations.